Some social psychological facors related to the attitude of fisherfolks toward selected fishery ordinances in Altavas, Aklan - Elumba, Ma. Christina E.
The study sought to demonstrate some social psychological factors which are related to the attitude of fisherfolks toward fishery ordinances in Altavas, Aklan. The variables that were correlated with the attitude toward fishery ordinances were perceived impact of the ordinances, perceived coastal resource base condition and personal involvement with coastal related income generating activites. The research design of this study was non-experimental. An interview method was used in gathering data. Thirty (30) fisherfolks in Brgy. Odiong and another thirty (30) fisherfolks in Brgy. Cabugao served as respondents. Results were analyzed using Spearman Rank Correlation statisitc. The result were made as follows: atitude toward the fishery ordinances is directly related to perceived impact of fishery ordinances, attitude toward fishery ordinances is inveresely related to perceived coastal resource base condition and attitude toward fishery ordinances is directly related to involvement with coastal related income generating activities